NCOG-14. INTRAOPERATIVE COGNITIVE-LINGUISTIC MAPPING GUIDED BY VISUALIZATION OF GAMMA BAND MODULATION ELECTROCORTICOGRAMS: PROOF OF CONCEPT IN A PATIENT WITH LEFT TEMPORAL AND OCCIPITAL LOW-GRADE ASTROCYTOMA. (14th November 2022) - Noll, Kyle; Asman, Priscella; Connelly, Katherine; Tasnim, Israt; Swamy, Chandra; Ene, Chibawanye; Sudhakar, Tummala; Grasu, Roxana; Liu, Ho-Ling; Kumar, Vinodh; Muir, Matthew; Prinsloo, Sarah; et al.
Abstract: OBJECTIVE: Determine the feasibility and preliminary utility of a novel approach to intraoperative brain mapping guided by visualization of electrocorticography (ECoG) heat maps. METHODS: A 39-year-old male with a biopsy-proven left posterior temporal and occipital WHO grade II IDH-mutant astrocytoma underwent awake craniotomy with intraoperative language mapping. Language mapping utilized a dual iPad stimulus presentation system (NeuroMapper) coupled to a portable real-time neural signal processing system capable of both recording cortical activity and delivering direct cortical stimulation in a closed-loop fashion. An ECoG grid (4x8 with 1cm pitch) which covered the majority of the left temporal lobe was used to assess oscillatory cortical activity during administration of language paradigms including object, action, auditory descriptive, and written descriptive naming. ECoG recording and cortical stimulation were synchronized with stimulus presentation via a photosensor attached to the patient-facing tablet. Gamma band modulations in response to language paradigms at each electrode were processed in real-time and visualized as heat maps in MATLAB/Simulink. Following recording and visualization, bipolar direct cortical stimulation from the grid was conducted for each neighboring electrode pair (up to an intensity of 6 mA) during administration of language tasks. RESULTS: Despite mild fluent aphasia, a large set of reliable baseline stimuli were obtained for the language mapping paradigms. All naming paradigms resulted in strongest heat map activation at electrode 12 located in the anterior to mid superior temporal gyrus. During stimulation, consistent speech arrest was observed across all paradigms when stimulating electrode pair 11-12, indicating good correspondence with ECoG heat map recordings. Additionally, this region corresponded well with posterior language network representation via resting-state fMRI. CONCLUSION: Intraoperative real-time visualization of task-based ECoG gamma band modulation is feasible and may help identify targets for direct cortical stimulation. If validated, this may improve the efficiency and accuracy of intraoperative language mapping.